Identifikasi Lalat Buah pada Tanaman Pare (Momordica charantia L.) di Kelompok Tani Tunas Muda Buraen Kelurahan Buraen Kecamatan Amarasi Selatan Kabupaten Kupang - Martyn Bunga Radja Riwu; Petronella S. Nenotek; Don H. Kadja; Rika Ludji (Wana Lestari, 2024)
This research aims to determine the types of fruit flies that exist in bitter melon cultivation belonging to the Tunas Muda Buraen Farmers Group, Buraen Village, South Amarasi District, Kupang Regency. This research was carried out on land belonging to the Tunas Muda Buraen Farmers Group, Buraen Village, South Amarasi District, Kupang Regency and the Plant Pest Laboratory, Faculty of Agriculture, Nusa Cendana University in August-November 2024. The fruit flies obtained from the traps were Bactrocera dorsali, Bactrocera papayae, and Bactrocera carambolae. However, the species obtained from rearing is the Bactrocera cucurbitae species, this species is a different species from the existing trap results. The different results are thought to be because the species obtained had different hosts, or the main host was not the bitter melon plant. The second factor is because the rearing activity does not use all the fruit that is attacked, thus giving the possibility that the unused fruit has been attacked by fruit flies, and the last factor is because the traps have been set early so there is little chance for other species to attack the bitter melon plants. From these factors, it is proven that the B. cucurbitae species damages bitter melon plants with the intensity of damage to bitter melon fruit being expressed as light damage intensity with an assessment of 6.21%.